Giant magnetocaloric effect near room temperature in the off-stoichiometric Mn–Co–Ge alloy. (17th November 2016) - Sharma, V K; Manekar, M A; Srivastava, Himanshu; Roy, S B
Abstract: We report a giant magnetocaloric effect near room temperature in an off-stoichiometric Mn–Co–Ge alloy, across the magnetostructural transition. The isothermal entropy change accompanying this transition has a peak value of nearly 40 J kg −1 K −1 near 297 K for a field excursion of 70 kOe, and a refrigerant capacity of 270 J kg −1 with the hot end at 302.5 K and cold end at 293.5 K. We also present an experimental protocol to avoid spurious peaks in the magnetocaloric effect across a sharp first order magnetostructural transition, not confined to Mn–Co–Ge alone, where metastability during the transition could influence the measured magnetization and thus the estimated entropy change. The estimated entropy change in the present off-stoichiometric Mn–Co–Ge alloy is possibly the highest reported value near room temperature in undoped Mn–Co–Ge alloys and underlines the potential of the alloy for technological applications in room temperature magnetic refrigeration.